2017
DOI: 10.1002/hep4.1063
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐induced steatosis involves impairment of lipophagy, associated with reduced Dynamin2 activity

Abstract: Lipid droplets (LDs), the organelles central to alcoholic steatosis, are broken down by lipophagy, a specialized form of autophagy. Here, we hypothesize that ethanol administration retards lipophagy by down‐regulating dynamin 2 (Dyn2), a protein that facilitates lysosome re‐formation, contributing to hepatocellular steatosis. Primary hepatocytes were isolated from male Wistar rats fed Lieber–DeCarli control or ethanol (EtOH) liquid diets for 6‐8 weeks. Hepatocytes were incubated in complete medium (fed) or nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…161 An additional mechanism that could underlie reduced autophagy following chronic alcohol exposure is the inactivation of the small guanosine triphosphate Rab7 and reduced dynamin 2 activity, which causes depletion of lysosomes and inhibits hepatocyte lipophagy. 165,166 Finally, inhibition of AMPK by alcohol results in decreased mitochondrial beta-oxidation and increased lipogenesis. 167 Additional anti-inflammatory effects of autophagy in macrophages are likely to reduce cytokine production by macrophages and therefore to block neutrophil recruitment to the liver (Fig.…”
Section: Key Pointmentioning
confidence: 99%
“…161 An additional mechanism that could underlie reduced autophagy following chronic alcohol exposure is the inactivation of the small guanosine triphosphate Rab7 and reduced dynamin 2 activity, which causes depletion of lysosomes and inhibits hepatocyte lipophagy. 165,166 Finally, inhibition of AMPK by alcohol results in decreased mitochondrial beta-oxidation and increased lipogenesis. 167 Additional anti-inflammatory effects of autophagy in macrophages are likely to reduce cytokine production by macrophages and therefore to block neutrophil recruitment to the liver (Fig.…”
Section: Key Pointmentioning
confidence: 99%
“…It is known that the activity of Dyn2 increased after it is phosphorylated by Src kinase, a non-receptor protein tyrosine kinase. In the second study performed by McNiven and Casey’s group, they utilized similar models to determine the role of Dyn2 in lipophagy after alcohol exposure as showed in the first study (11). They found that the phosphorylated (active) forms of Src and Dyn2 decreased in hepatocytes isolated from chronic alcohol-fed rats compared with the hepatocytes from pair-fed control rats.…”
mentioning
confidence: 99%
“…Alcohol-induced fatty liver was reported in humans (Buck, 1948) decades before the metabolic pathways affected by heavy drinking were revealed and well before it was discovered that certain fatty acids are hepatotoxic (Savary et al, 2012). Hepatic fatty acid (and lipid droplet) accumulation after alcohol abuse arises from: (1) accelerated hepatic lipogenesis (You et al, 2002; You and Crabb, 2004); (2) enhanced fatty acid import into the liver from the plasma (Wei et al, 2013); (3) defective secretion of lipoproteins (e.g., very low density lipoproteins VLDLs) from the liver into the plasma, resulting in their hepatic retention (Kharbanda et al, 2009); (4) reduced fatty acid oxidation (FAO) by mitochondria (Fischer et al, 2003); and now, (5) decelerated lipophagy (Rasineni et al, 2017; Schulze et al, 2017a).…”
Section: Metabolic Sources Of Alcohol-induced Hepatic Lipids and Theimentioning
confidence: 99%